Ohmic Contact characterization Using Image Processing - Shashikala B.N.; Nagabhushana B.S. (International Journal of Electrical and Computer Engineering (IJECE), 2015)
The Ti/Al/Ni/Au films deposited by electron beam evaporation on n type GaN was demonstrated as a suitable solution for low resistive and thermally stable contact to n-type GaN. The surface morphology of Ti/Al/Ni/Au and Ti/Al contacts were studied as a function of the annealing process conditions using image processing techniques. The algorithm was implemented using the MATLAB software. Using the algorithm made, the area occupied by the pores and porosity in the ohmic contact structures were obtained.